PENGARUH KECERDASAN EMOSIONAL, MOTIVASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA GURU TAMAN KANAK-KANAK SE-KECAMATAN MANTRIJERON (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Emotional Intelligence, Motivation and Leadership on Job Satisfaction of the Kindergarten Teachers in Mantrijeron Subdistrict Thesis. Educational Administration Program, Postgraduate of Sarjanawiyata Tamansiswa University, Yogyakarta 2013.The study aims to: (1) determine the influence of emotional intelligence on job satisfaction of the kindergarten teacher in Mantrijeron District, (2) determine the influence of motivation on job satisfaction of the kindergarten teacher in Mantrijeron District, (3) determine the influence of leadership on job satisfaction of the kindergarten teacher in Mantrijeron District, and (4) determine the influence of emotional intelligence, motivation and leadership on job satisfaction of the kindergarten teacher in Mantrijeron District.This study is quantitative study. The population in this study was all kindergarten teachers in Mantrijeron District of Yogyakarta with totaling 75 people. The sampling in this study using census technique or the total sample. The technique collection of data using a questionnaire which includes emotional intelligence, motivation, leadership and job satisfaction. The data analysis technique used was multiple linear regression analysis to determine the effect of independent variables simultaneously on the dependent variable. Testing requirements include normality, linearity and multicollinearity. The test results for normality with the Kolmogorov-Smirnov test showed that all variables were normally distributed. The results of linearity test with F test showed that the correlation of independent variables and the dependent variable was expressed linearly. The result of multicollinearity test with VIF showed was no symptoms multicollinearity between independent variables.The result showed the following results: (1) There is the influence of emotional intelligence on job satisfaction of the kindergarten teacher in Mantrijeron District by 12.1%, (2) There is the influence of motivation on job satisfaction of the kindergarten teacher in Mantrijeron District by 12.7% (3) There is the influence of leadership on job satisfaction of the kindergarten teacher in Mantrijeron District by 9.8%, and (4) There is the influence of emotional intelligence, motivation and leadership on job satisfaction of the kindergarten teacher in Mantrijeron District by 34.6%.